Recurrent hyperparathyroidism: a study of 3 cases with evaluation of some pathogenetic and clinical aspects. Issue 737 (March 1987) - Mazzuoli, G.; Minisola, S.; Scarda, A.; De Matteis, A.; Tabolli, S.; Bigi, F.; Valtorta, C.; D'Erasmo, E.
Abstract : Three patients with recurrent hyperparathyroidism (15, 8 and 3 years respectively, after the first operation) are described in order to establish the causes and define the clinical characteristics of the disease. The observation that in the present series recurrent hyperparathyroidism was associated either with an adenoma (two cases) or a carcinoma (one case), appears to stress the possibility of the pathological involvement of one gland even though recurrent hyperparathyroidism should be considered due to the chronic extrinsic stimulation of the parathyroid glands. The severity of the clinical and metabolic picture observed at the time of the first diagnosis and/or at the time of recurrence together with the simultaneous presence of bone and stone disease in the patients described is of particular interest. The cases reported underline the importance of carrying out careful metabolic investigations in patients with hyperparathyroidism not only before but also for a prolonged period of time after operation.